2019
DOI: 10.1111/hex.12862
|View full text |Cite
|
Sign up to set email alerts
|

A realist evaluation of a regional Dementia Health Literacy Project

Abstract: Background A Dementia Health Literacy Project was undertaken in the north coast region of NSW, Australia, after it was identified as having a high prevalence of dementia. A Dementia Support Kit was produced with service user engagement to provide useful information to people with dementia and their families. Objective To evaluate the Dementia Health Literacy Project using a realist evaluation framework. Setting and participants The setting was the region of the north coast of New South Wales. Eight people diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…130 papers were identified of which 16 studies were retrieved for inclusion. The studies documented PPI involvement from the researcher's perspective (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), through analysis of workshop and advisory committee minutes (19,20) or by directly asking PPI representatives for their experiences (21*, 22**).…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…130 papers were identified of which 16 studies were retrieved for inclusion. The studies documented PPI involvement from the researcher's perspective (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), through analysis of workshop and advisory committee minutes (19,20) or by directly asking PPI representatives for their experiences (21*, 22**).…”
Section: Search Resultsmentioning
confidence: 99%
“…Only four studies involved a broader range of stakeholders including caregivers, the public, PLWD and carer support workers recruited via existing links with the research team, a national dementia organisation and a University volunteering service (22**). One study involved members of the public, PLWD and caregivers, however it was unclear how they were approached (14*), while another involved PLWD, their caregivers, older adults without dementia and healthcare professionals from local groups and services (10). One study ran groups with people affected by early onset dementia and their caregivers recruited through national dementia support groups, and also interviewed health professionals and voluntary sector workers (7).…”
Section: Who Was Involved?mentioning
confidence: 99%
See 2 more Smart Citations
“…Confirming other research, MEDREV found that carers require training in the use of medication and the management of behaviours that challenge (Grace and Horstmanshof, 2019;Maidment et al, 2017). Person-centred care is frequently Table 3.…”
Section: Discussionmentioning
confidence: 59%